Multilevel Parking Berbasis Mikrokontroler - Triyadi, M Dico; Zulkarnain, Ade; Tommy, Tommy; Asih, Munjiat Setiani (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
Throught science and technology (Science and technology) that us increasingly developing now a days, more and more using human technology. With the technology it can help humans in every day life. But in technology area, there all stull system that use manual methods such as parking. The impact of indiscriminate parking casuses quite severe congestion, not to mention the illegal parking fees quoted in the name of government based on the problems outlined, as solution is found to find the existence og indiscrimimate parking. That way conducted research on “Multilevel parking based on Mikrocoontroller”. Mulitilevel can be interpreted with multilevel or tierd sentences. The parking lot does not move because the vehicle is being moved by driver. Microcontroler has a system that is intended to recive input from what has been made and made to be an input.